Panoramic technique in the video monitoring system and Implementation - Yun Liu; Jiru Zhang; Jian Gao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Video surveillance technology plays an important role in the security field, with its intuitive, convenient and abundant information and is widely used in city traffic, civil security and other various fields especially in the important safety departments or major events. In this paper, according to the video surveillance system features and functional requirements, we use embedded system ,OMAP4460 and Android operating system on the basis of the panoramic technology to realize vertical 180 degrees horizontal 360-degree panoramic video surveillance. In the paper we profoundly analyze and discuss the embedded panoramic video surveillance system mainly from the hardware platform structures, the design of the peripheral circuit and the panorama function implement. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1874